Monetary Policy Analysis and Forward-Looking Taylor Rule - Šilhart, Marek (2019)
The objective of this thesis is to report the estimation of the forward-looking Taylor rule for the European central bank (ECB) from the time of its establishment in 1999 to the time of Expanded Asset Purchase Programme, launched at the beginning of 2015, and use it for monetary policy analysis. The estimation is performed by the generalized method of moments. The baseline model is formulated and the robustness to changes in horizons of the inflation and output gap forecasts and changes of instrumental set is performed. As the last step additional regressors are added to the baseline model. According to the estimation of the baseline, the ECB changes nominal interest rate in reaction to both the expected inflation and the output gap deviations. The estimation of the baseline model with interest rate inertia assumption which seems to be more robust than the second one without interest rate inertia assumption, suggests that the ECB reacts to changes in the expected inflation by increasing the nominal interest rate sufficiently enough for the real rate to be increased as well. With interest rate inertia assumption the estimated inflation target, officially defined as “below but close to 2 %“, is 1.38 % for inflation measured by HICP and 1.85 % when a proxy of core HICP is used to measure the inflation. The deviation of the actual path of the interest rate from the interest rate path resulting from the Taylor rule without the smoothing term suggests, that the launch of the Expanded Asset Purchase Programme in 2015 was rather a discretionary reaction of the central bank.